Analisa Keseimbangan Energi PLTU Takalar (Punagaya) Unit 2 Berdasarkan Perubahan Beban - Makmur Saini; Nur Hamzah; Devi Prasetyo Utomo (Jurnal Teknik Mesin Sinergi, 2020)
This study aims to calculate the efficiency and heat rate of the unit 2 PLTU Takalar (Punagaya) system with the energy balance calculation method, calculate the NPHR value of PLTU Takalar (Punagaya) unit 2 when the unit is operating, and also to determine the energy loss from the conversion energy results at PLTU Takalar (Punagaya) unit 2 when the unit operates. The PLTU's Net Plant Heat Rate (NPHR) value is a very important role as an indicator of the performance of a steam power plant. The real-time NPHR value calculation using the energy balance method can be used as an evaluation material to control the operation pattern of the generator in order to obtain optimal operation. The method used in this research is to collect direct and indirect data to calculate the energy balance and NPHR of PLTU Takalar (Punagaya) unit 2 during the reliability run period. The calculations carried out include the calculation of the energy balance in the boiler, the energy balance in the steam cycle, the balance of electrical energy, the efficiency of the PLTU and NPHR systems. Based on the results of calculations that have been carried out the efficiency and NPHR of PLTU Takalar (Punagaya) unit 2 is the best during the reliability run of 32.76% and 2801.93 kcal / kWh at full load conditions with an energy loss value of 220.60 MW. The performance of PLTU Takalar (Punagaya) unit 2 during the reliability run is very good where the unit operates continuously and the NPHR value when full load fulfills the contract warranty and the maximum operating target.